The Batang Arau Village Program in Padang Selatan District, Padang City in Enhancing the Community's Economy Post-COVID-19 - Yendra, Musfi; Kusuma, Doddie Arya; Handrina, Emi; Wahyudi, Wahyudi; Alamsyah, Dodi Saftian; Rivaldi, Rivaldi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research is motivated by the Covid-19 pandemic which has had a major impact on the economy of the community in Batang Arau Village. Factors such as lack of access to good jobs, lack of skills, and infrastructure problems are major obstacles to local economic progress. The socio-economic conditions in Batang Arau Village show that a small portion of its population still faces difficulties in earning enough income to meet their daily needs. This condition is exacerbated by the local economic sector which is usually limited to micro and small businesses, which still have difficulty gaining access to a wide market. By providing various development programs, the Padang city government has tried to improve community welfare. However, these efforts have not been able to fully solve the economic problems in Batang Arau Village. The problems in this study are (1) What are the Economic Conditions of the Batang Arau Village Community during Covid-19. (2) What programs has the Batang Arau Village Government made to improve the community's economy after Covid-19. (3) What is the impact of the Batang Arau Village Government Program on improving the community's economy after Covid-19. This study uses a qualitative descriptive method with data collection techniques through observation and interviews with 13 informants selected by purposive sampling. The results of the study indicate that the Covid-19 pandemic has resulted in an economic decline in Batang Arau Village. The Batang Arau Village Government responded with various programs, such as social assistance, entrepreneurship training, and capital assistance. This program has a positive impact in terms of increasing family income through direct assistance, skills training, and business capital assistance, creating new jobs and reducing dependence on the informal sector, facilitating the emergence of new businesses and increasing the number of active entrepreneurs in Batang Arau Village.